2019
DOI: 10.3758/s13414-019-01700-z
|View full text |Cite
|
Sign up to set email alerts
|

Crowding in depth for binocular and monocular observation

Abstract: Crowding refers to the phenomenon of reduced recognition performance for peripherally presented targets that are flanked by similar stimuli. Crowding is known to vary with lateral distances (i.e., effects of target eccentricity and inter-character spacing). In the present experiment, we examined how crowding is affected by the distance of the stimuli in depth for natural viewing, i.e., for binocular observation of a real depth presentation. Superimposing the displays of two orthogonally arranged screens with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 53 publications
3
13
1
Order By: Relevance
“…Thus, with defocus blur as the only possibly available depth cue, flanker depth did not affect target recognition differentially. This replicates earlier findings [ 32 ] and is in line with the fact that all of the depths were within the depth of field [ 39 ]. Taken together, monocular data suggest that the observed effects of flanker depth are driven rather by binocular depth information than by defocus blur.…”
Section: Experiments 1: Effects Of Flanker Direction and Distance Isupporting
confidence: 92%
See 4 more Smart Citations
“…Thus, with defocus blur as the only possibly available depth cue, flanker depth did not affect target recognition differentially. This replicates earlier findings [ 32 ] and is in line with the fact that all of the depths were within the depth of field [ 39 ]. Taken together, monocular data suggest that the observed effects of flanker depth are driven rather by binocular depth information than by defocus blur.…”
Section: Experiments 1: Effects Of Flanker Direction and Distance Isupporting
confidence: 92%
“…Thus, one interesting question is to what extent flankers are processed when they deviate in depth. The data of monocular observation in Experiment 1 showed that flanker resolution due to defocus blur has no impact within the present range in depth, replicating earlier findings [ 32 ] and supporting what would be expected from the literature on depth of field (e.g., [ 39 ]).…”
Section: Post-hoc Analysis For Experiments 1 Andsupporting
confidence: 89%
See 3 more Smart Citations